Statelessness a modern history - Mira L. Siegelberg (Cambridge, Massachusetts Harvard University Press, 2020)
Two world wars left millions stranded in Europe. The collapse of empires and the rise of independent states in the twentieth century produced an unprecedented number of people without national belonging and with nowhere to go. Mira Siegelberg?s innovative history weaves together ideas about law and politics, rights and citizenship, with the intimate plight of stateless persons, to explore how and why the problem of statelessness compelled a new understanding of the international order in the twentieth century and beyond.
Includes index
Keywords: Statelessness